Synergy of Inclusive Groups as An Effort to Resolve Identity Politics in Elections - Hilyatul Asfia; Putri Fansiska Purnama Pratiwi (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2023)
The practice of identity politics by exploiting the issue of SARA in the 2019 simultaneous election contestation has damaged the essence of democracy. This raises problems that threaten the unity and integrity of the Indonesian nation so it has implications for constituents in exercising their right to vote. Factors of diversity, structure and legal culture that are still weak are the main problems that demand to be resolved. This research focuses on efforts to gather and strengthen inclusive groups, namely active participation by the government, mass media, students and the community through a series of strategic steps in carrying out their functions. This study uses a type of normative research with secondary data types. Based on a philosophical, statutory and conceptual approach. From the research conducted, it was found that the synergy of internal (government) and external (community) roles based on the legal system in an inclusive manner is a step to overcome and resolve the problem of using SARA issues in attracting the votes of sympathizers, to create quality democracy.The practice of identity politics by exploiting the issue of SARA in the 2019 simultaneous election contestation has damaged the essence of democracy. This raises problems that threaten the unity and integrity of the Indonesian nation so it has implications for constituents in exercising their right to vote. Factors of diversity, structure and legal culture that are still weak are the main problems that demand to be resolved. This research focuses on efforts to gather and strengthen inclusive groups, namely active participation by the government, mass media, students and the community through a series of strategic steps in carrying out their functions. This study uses a type of normative research with secondary data types. Based on a philosophical, statutory and conceptual approach. From the research conducted, it was found that the synergy of internal (government) and external (community) roles based on the legal system in an inclusive manner is a step to overcome and resolve the problem of using SARA issues in attracting the votes of sympathizers, to create quality democracy.